Electrostatic pneumatic spraying on ‘Niagara Branca’ and ‘Rosada’ grapevines - Stawniczyi, Tiago Jose Reis; Lima, Cláudia Simone Madruga; Trevisan, Fernando; Pinto, Vânia Zanella (Revista de Ciências Agroveterinárias, 2019)
Vine cultivation is the target of several pathogens such as fungi, against which synthetic fungicides are commonly used, so studies have been made on methods to decrease the volume of pesticides to reduce problems such as phytotoxicity, costs and environmental damage. Thus, the objective of this research was to verify the effect of electrostatic pneumatic spraying on Niagara Branca and Rosada grapevines in Laranjeiras do Sul, PR. Fungicidal treatment was carried out on grapevine cultivars (Niagara Branca and Rosada), applying them with present and absent load. The application volume, the seed coat, the severity of diseases in plants and bunches, number of bunches and bunches with lesions per plant, number of berries per bunch, length and bunch diameter, fresh mass, soluble solids, titratable acidity, fruit epidermal coloring, total phenolic compounds, total anthocyanins, loss of mass, and determination of appearance. This study was conducted under a completely randomized blocks design, for field variable responses and physical-chemical and phytochemical characterization of fruits, consisting of two factors (2x2), a load factor and another cultivar. For the variables loss of mass and determination of appearance, the factorial scheme was 2x2x5, where Niagara cultivar and storage periods (0, 2, 4, 6 and 8 days) were a load factor. The data were subjected to analysis of variance, and when significant they were compared by the Tukey test (p<0.05) through the statistics software Assistat. Different cultivars showed mass of the affected fruits in different ways, as well as the appearance of the fruits, according to the storage periods evaluated. Spraying with the presence of filler had an effect on the color of the epidermis and bunch length on 'Niagara Branca', also promoted a higher content of anthocyanins and resulted in a lower volume of spray solution applied with indifferent coverage, and therefore electrostatic spraying showed an effect on the application.